KEKARAENGAN RUMBIA: Study of the Traditional Turatea Government System in Jeneponto - Ismail Syawal (Universitas Syiah Kuala, 2023)
Abstract: Rumbia is one of the regions of the Turatea Kingdom in Jeneponto which has a traditional government system called kekaraengan. This research was conducted to find out how the traditional government system “ke karaengan” of Rumbia and why karaeng is no longer common in Turatea. This study uses historical methodology through four main steps of the historical method, namely: heuristics, source criticism, interpretation, and historiography. The results showed that (1) Rumbia's karaengan was formed through the concept of tumanurung which is a symbol of the life of its supporting community, (2) Rumbia has a Customary Council from a unitary of four villages called Bakuq Appaka or Pangngadakkan, (3) Rumbia's karaengan underwent changes when the Dutch succeeded in controlling the area in 1863.